The Influence of Content Marketing and Social Media Marketing on Customer Satisfaction in F&B Business in Indonesia - Deriyana Saputra; Alfatih S. Manggabarani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The development of digital technology has encouraged changes in marketing strategies in the Food and Beverage (F&B) industry in Indonesia through the use of content marketing and social media marketing as a means to build relationships with consumers and increase customer satisfaction. Although both digital marketing strategies are increasingly being applied, the results of previous research still show inconsistencies regarding their effect on customer satisfaction. Therefore, this study aims to analyze the influence of Content Marketing and Social Media Marketing on Customer Satisfaction in F&B business in Indonesia. This study uses a quantitative approach with purposive sampling techniques on 120 respondents who have made purchases in the F&B business in Indonesia. The data was analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS-SEM) with the help of SmartPLS 4 software. The results of the study showed that Content Marketing had a positive and significant effect on Customer Satisfaction with a T-Statistic value of 5.176 and a P-Value of 0.000. In addition, Social Media Marketing also has a positive and significant effect on Customer Satisfaction with a T-Statistic value of 4,750 and a P-Value of 0.000. The Adjusted R-Square value of 0.533 indicates that the two independent variables are able to explain 53.3% of the variation in Customer Satisfaction, while the remaining 46.7% are influenced by other variables outside the research model. These findings indicate that the implementation of quality content marketing and effective social media marketing activities play an important role in increasing customer satisfaction, so that it can be a relevant strategy for F&B business people to strengthen competitiveness in the digital era.